Early axial and appendicular skeletal development of the meagre (Argyrosomus regius). A comparison of two rearing systems - Valles, E. (2014)
The meagre (Argyrosomus regius) is a new species for aquaculture with high economical value, presenting growth rates of 1 kg/year. Skeletal deformities generally appear in cultured larvae at early stages, reducing the value of the fish. The present study describes the osteological development of the vertebral column and fins in meagre larvae. Meagre larvae were obtained from wild broodstocks, kept at IRTA and IPIMAR, and induced to spawn using GnRHa injection.